আমরা কি এই বাঙলাদেশ চেয়েছিলাম - আজাদ,হুমায়ুন. 1947- (ঢাকা : আগামী প্রকাশনী, 2003)
On gradual falling standards of administration and political conflicts within Bangladesh.
In Bengali.
Keywords: Bangladesh -- Politics and government -- 1971-